Creation of Bone and Soft Tissue in Postmaxillectomy Patients Using Curvilinear Transport Distraction Osteogenesis - Hendricks, Rushdi (Ann Maxillofac Surg, 2019)
BACKGROUND: Large surgical defects in the maxilla due to trauma or tumor are usually reconstructed with revascularized-free fibula flaps (RFFF). In the past, the use of curvilinear transport distraction osteogenesis (CTDO) has been shown to be an efficacious way in closing large defects in the maxilla, but it had limitations which have now been overcome by the present development. The present distractor is an improvement upon the previous three prototypes and employs the concept of tetrafocal distraction by means of hybridizing the bone with the tooth in the transport disc segment. This article aims to prove that tetrafocal distraction provides a viable alternative to the RFFF. MATERIALS AND METHOD: In a prospective cohort study of six postmaxillectomy patients, the method of CTDO was applied and investigated to ascertain the outcome. The regenerate bone was compared with the parent bone, using a new maxillary transport distractor. A linear bicortical fracture was created in the maxilla in a vertical direction (segmentally) to develop a mobile, vascularized transport disk. This transport disk underwent further subdivision to produce the concept of tetrafocal distraction. RESULTS: After osseointegration of the dental implants, prosthetic rehabilitation of the dentition was successful. The authors report the successful outcome of two of the six cases subjected to CTDO to treat defects ranging from 25 mm (using bifocal distraction) to 80 mm along a curved trajectory (using tetrafocal distraction). CONCLUSIONS: The production of curvilinear bone and soft tissue along a horizontal plane has been demonstrated. From a clinical perspective, the new alveolar bone achieved the correct width and height to create a physiological vestibule and an esthetic zone for dental implants. In addition, the shape of the palatal vault is also reconstituted. The tetrafocal method of the CTDO is a reliable method of maxillary reconstruction.